2015
DOI: 10.5350/dajpn2015280101
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnosis and sociodemographic characteristics of patients admitted to psychiatry clinic in a rural area

Abstract: Psychiatric diagnosis and sociodemographic characteristics of patients admitted to psychiatry clinic in a rural areaObjective: There is little published literature about the characteristics of patients with mental disorders in rural hospitals. The aim of this study is to determine the mental illness and the demographics of the patients who admit to the outpatient policlinic that offers psychiatric health service for the first time in a rural state hospital. Method:The semi-structured interview consisting DSM-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…In a study investigating the distribution of diagnosis of psychiatric disorders in a rural region having a psychiatric service for the first time and the relationship between these diagnoses and sociodemographic characteristics, it was reported that there was no relationship between psychiatric diagnoses of the individuals and their places of residency. 21,29 Our results support the relevant data in the literature. This situation shows that diagnostic groups can be observed in every society and region as a result of differentiation in nutrition styles, and living and environmental conditions with the rapid spread of globalization and technological developments, also in Turkey.…”
Section: Discussionsupporting
confidence: 89%
“…In a study investigating the distribution of diagnosis of psychiatric disorders in a rural region having a psychiatric service for the first time and the relationship between these diagnoses and sociodemographic characteristics, it was reported that there was no relationship between psychiatric diagnoses of the individuals and their places of residency. 21,29 Our results support the relevant data in the literature. This situation shows that diagnostic groups can be observed in every society and region as a result of differentiation in nutrition styles, and living and environmental conditions with the rapid spread of globalization and technological developments, also in Turkey.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with previously published reports (6,8-10). For example, Eda Aslan Uckardes demonstrated that 67.2% of patients who applied to psychiatry outpatient clinic in a rural area were women (8). We found a similar rate of woman admission despite diverse living areas of populations.…”
Section: Discussionsupporting
confidence: 58%
“…Uckardes detected comorbid medical conditions with a rate of 29.4% in patients with psychiatric disorders and stated that the most common comorbid disease was HT and the second most common DM (8). In our study, almost one to five patients had any comorbid disease.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations